Does prison location matter for prisoner wellbeing? The effect of surrounding greenspace on self-harm and violence in prisons in England and Wales - Dominique Moran; Phil I Jones; Jacob A Jordaan; Amy E Porter (Wellbeing, Space and Society, 2022)
Research on prison location primarily focuses on relationships with local communities and the impact of distance on visitation. Considering the issue of prison location in a different manner, this paper deploys GIS methodology to determine whether the characteristics of prison location can impact prisoners themselves. The presence of greenspace, blue space and major roads in a 500m buffer zone surrounding prisons in England and Wales was calculated using Geographical Information Systems (GIS). An econometric analysis was then undertaken examining this location data in relation to official statistics on violence and self-harm at the institutional level. Econometric estimations confirmed that there are lower levels of self-harm and violence in prisons with higher percentages of greenspace in the buffer zone. These relationships are statistically robust, and they persist when we control for prison size, type, age, and level of crowding. The findings suggest that prisoners may be influenced by the characteristics of prison sites, and that accordingly, these characteristics should be considered when locations for future prisons are selected. Based on these initial findings, we outline the potential for future research to further examine the effect of environmental features on individuals to whom they are not visible.